(3GdeUHGM aj GdfMhs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Pi GdCfYGe LGYd GdfMh ai GdcdGe cGdedM ai GdWYGe aEf GdhdO GdCYR dGRGd cGSeg eSYhOkG deG ESJXgQ eNJUQ GdEbfGY aGSJUajJ efgG gPG GdeNJUQ s
(3BNQgG (B:s
(3hjbGd HCfgG ddTc ai GdNHQ hddJNjjQ hGdEHGMI ai GdCeQ fMh NP gPG Ch PGc hLGdS GdMSf Ch GHf SjQjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B71 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B488s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1708s
Keywords: (3GdfMhs